Clinical analysis using proximal femoral locking plate in the management of complex, comminuted pertrochanteric femoral fractures in adults: a prospective study - Muqtadeer Abdul Aziz, Ansari; Jaju, Rahul Gopikishan; Lokhande, Milind (International Journal of Research in Orthopaedics, 2018)
Background: Pertrochanteric fractures consume major part of orthopaedic injuries with high morbidity and cost factors. They affect almost all age groups. The treatment options vary a lot depending on the type of fracture and age. Despite marked improvement in implant design, surgical technique and patient care; pertrochanteric fractures continue to consume a substantial proportion of our health care resources. Methods: This prospective study consists of 20 adult patients of pertrochanteric fractures of femur, who were treated with internal fixation using PFLP. All patients were followed up at an interval of 4 to 6 weeks till fracture union and then once in 3 months till 1 year. Results: Anatomical results are noted as good or poor depending upon shortening, varus deformity, hip movements and knee movements and functional result as excellent, good, fair and poor depending upon the hip pain, ambulatory status, ability to squat, and sit cross leg. In the study 2 patients had shortening of l cm. None of the patients had any varus deformity. Overall excellent to good results were achieved in 85% cases. Conclusions: The potential advantages of the proximal femoral locking plate over intramedullary devices are better biomechanical design, ability to bear more stress due to, strong biomechanical stability shows that this technique holds considerable promise in complex, comminuted fractures in revision cases and in osteoporosis.